The case for the central bank independence - DE HAAN, J.; STURM, J.E. (PSL Quarterly Review, 2013)
The position of the European System of Central Banks (ESCB) is an important issue in the process towards European economic and monetary union (EMU). At the December 1991 meeting in Maastricht, the European council decided that the primary objective of the ESCB shall be to maintain price stability. This paper explores the influence of central bank independence on the level and variability of inflation, the level and financing of government budget deficits, and on economic growth. JEL: E58